The new lesbian aesthetic? Exploring gender style among femme, butch and androgynous sexual minority women - Gunn, Audrey; Hoskin, Rhea Ashley; Blair, Karen L. (Women's Studies International Forum, 2021)
The current study explored sexual minority women’s gender aesthetic and style by using van Anders’ (2015) sexual configurations theory (SCT), which allows for nuance in the measurement of gender/sex research. Previous research on sexual minority women has suggested a markedly masculine “Lesbian Aesthetic” (Huxley et al., 2014) and has connected aesthetic expression to internalized homophobia and levels of outness such that sexual minority women categorized as more feminine report higher rates of internalized homophobia and identity concealment. However, the bulk of past research used dichotomous measures of assessing gender and predated an ostensible shift in LGBTQ+ identities. To update this body of research, the current study explored gender aesthetics by asking sexual minority women to map their gender expression using SCT diagrams and complete measures of outness and internalized homophobia. We found no significant group differences in internalized homophobia or outness for femme, butch, and androgynous participants. Content analyses of gender diagrams suggest that the gender aesthetics of sexual minority women are neither monolithic nor masculine but may be beginning to lean towards the feminine and most certainly encompass a complex and diverse range of expressions
Keywords: amériques; approches et analyses; canada; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; lesbophobie; psychologie; queer; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppression

The lived experiences of black undergraduate lesbian students at a rural South African university - Nela, K.; Vawdab, N.; Mbokodoc, L.; Govender, S. (Gender and Behaviour, 2017)
Malgré l'acceptation croissante des personnes lesbiennes, gays, bisexuelles, transgenres et intersexes (LGBTI), de nombreuses études indiquent encore que de nombreuses discriminations existent toujours. Les lesbiennes d'Afrique australe sont quotidiennement victimes de violences physiques et verbales et de viols correctifs. Le but de cette étude était d'explorer les expériences vécues par des étudiantes lesbiennes noires de premier cycle dans une université rurale en Afrique du Sud. Une approche de recherche qualitative utilisant un plan de recherche phénoménologique a été utilisée. L'échantillon était composé de quinze étudiantes lesbiennes noires de premier cycle âgées de 18 à 25 ans. Les données ont été collectées dans deux groupes de discussion et analysées à l'aide d'une analyse phénoménologique interprétative (IPA). L'homophobie, le harcèlement, y compris les agressions physiques, et la non-acceptation étaient des expériences quotidiennes chez les participantes lesbiennes. Cela incluait la discrimination de la part des pairs, du personnel universitaire et des organisations religieuses. Des expériences positives, comme la rencontre de nouveaux amis partageant la même orientation sexuelle et la découverte de l'université comme espace libre pour explorer leur sexualité, ont été trouvées.
Number: 3
Keywords: afrique; afrique du sud; approches et analyses; discipline; droits des femmes*; hétérosexisme; lesbophobie; personnes lesbiennes; psychologie; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppression; thématiques; violences; violences contre les femmes*; étudiantes de premier cycle